2009
DOI: 10.3945/ajcn.2008.26615
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of methylcobalamin and folinic acid treatment on glutathione redox status in children with autism

Abstract: The significant improvements observed in transmethylation metabolites and glutathione redox status after treatment suggest that targeted nutritional intervention with methylcobalamin and folinic acid may be of clinical benefit in some children who have autism. This trial was registered at (clinicaltrials.gov) as NCT00692315.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
219
4
13

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 221 publications
(249 citation statements)
references
References 39 publications
13
219
4
13
Order By: Relevance
“…The interdependence among folate, B12, and SAM and the importance of normal levels for optimal brain functioning has been discussed previously (Bottiglieri 2013). A 3 month open-label trial of injectable methyl B12 combined with folinic acid in 2009 in 40 children with ASD partially confirmed this hypothesis ( James et al 2009). Children supplemented with methyl B12 and folinic acid demonstrated significant increases in cysteine and glutathione (GSH) while reducing the oxidized inactive form of glutathione (GSSG), both consistent with improved antioxidant capacity.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…The interdependence among folate, B12, and SAM and the importance of normal levels for optimal brain functioning has been discussed previously (Bottiglieri 2013). A 3 month open-label trial of injectable methyl B12 combined with folinic acid in 2009 in 40 children with ASD partially confirmed this hypothesis ( James et al 2009). Children supplemented with methyl B12 and folinic acid demonstrated significant increases in cysteine and glutathione (GSH) while reducing the oxidized inactive form of glutathione (GSSG), both consistent with improved antioxidant capacity.…”
Section: Introductionsupporting
confidence: 54%
“…Interestingly, we did not find that methyl B12 improved measures of oxidative stress (GSH/GSSG), which was seen in a previous open-label trial of 40 children with ASD ( James et al 2009). In the previous study, James et al screened children for metabolic evidence of reduced methylation capacity (SAM/SAH) and reduced antioxidant capacity (GSH/GSSG) as an inclusion criterion to increase sensitivity, and included folinic acid as a combined treatment with the methyl B12.…”
Section: Methyl B12 For Autismmentioning
confidence: 56%
“…James et al 129 reported improvement in glutathione and S-adenosylhomocysteine levels following open-label administration of methylcobalamin (methyl B 12 ) and folinic acid; again, however, there was no clinical correlation. Two double-blind, placebo-controlled studies on dimethylglycine (a methyl donor with potential activity at NMDA receptors) showed no treatment effects on Vineland Adaptive Scores, Aberrant Behavior Checklist, or Children's Psychiatric Rating Scale scores.…”
Section: Biologically Based Practicesmentioning
confidence: 99%
“…Very early detection of Hcy metabolic problems and supplementation with these essential factors could be a positive step towards preventing autism spectrum disorders, and this is a strategy that might be considered in pediatric preventive medicine. Supplementation in older autistic children may help to re-establish a correct metabolic profile (20), but the development of the nervous system is already established and the brain is not able to reverse the damaging processes and recover.…”
mentioning
confidence: 99%